Developing Educational Statistics Module by Using Problem-Based Learning (PBL) for the Students of the Faculty of Teacher Training and Education of Bung Hatta University, Padang, Indonesia - ., Khairudin; Suryani, Karmila; D. Trisno George Selvi, A.; Hasanah, Uswatun (International Journal of Engineering and Technology, 2018)
This study aims to develop a Problem-Based Learning (PBL)-oriented module for Educational Statistics course, and to test whether or not such such module is feasible to be used as learning material for the students. The module was developed by applying ADDIE research and development model which includes the following stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The module eligibility was tested by media experts, materials experts, and students. The results of testing showed that the feasibility of the module according to the media and material experts are 82.6% and 87.9% respectively. In addition, the practicality tests in a small scale resulted in an average percentage of 85.03%, and the module effectiveness test obtained a percentage of 65%. Therefore, it can be concluded that the Educational Statistics module for the students is worth developing and feasible to be used as a guide in the learning process at the Faculty of Teacher Training and Education. Â